Plasma Clearance of B-Type Natriuretic Peptide (BNP) before and after Bariatric Surgery for Morbid Obesity. (31st December 2020) - Poh, Kian Keong; Shabbir, Asim; Ngiam, Jinghao Nicholas; Lee, Poay Sian Sabrina; So, Jimmy; Frampton, Christopher M; Pemberton, Christopher J; Richards, Arthur M
Abstract: Background: Obese patients have lower plasma concentrations of the cardiac natriuretic peptides (NPs) than their age- and sex-matched counterparts. This may reflect lower production and/or increased peptide clearance. It is unclear whether NP bioactivity is affected by obesity. Methods: We studied the effects of obesity on B-type natriuretic peptide (BNP) clearance and bioactivity by comparing results from standardized intravenous infusions of BNP administered 2 weeks before and 6 months after bariatric surgery in 12 consecutive patients with morbid obesity (body mass index, BMI > 35 kg/m 2 ). Anthropometric, clinical, neurohormonal, renal, and echocardiographic variables were obtained pre- and postsurgery. Pre- vs postsurgery calculated intrainfusion peptide clearances were compared. Results: BMI (44.3 ± 5.0 vs 33.9 ± 5.2 kg/m2, P < 0.001) and waist circumference (130.3 ± 11.9 vs 107.5 ± 14.7 cm, P < 0.001) decreased substantially after bariatric surgery. Calculated plasma clearance of BNP was reduced (approximately 30%) after surgery. Though not controlled for, sodium intake was presumably lower after bariatric surgery. Despite this, preinfusion endogenous plasma NP concentrations did not significantly differ between pre- and postsurgery studies. The ratio of plasma N-terminal (NT)-proBNP to 24 h urine sodium excretion was higher postsurgery ( P = 0.046; with similar nonsignificant findings for BNP, atrial NP (ANP) and NT-proANP), indicating increased circulating NPs for a given sodium status. Mean plasma NP concentrations for given calculated end-systolic wall stress and cardiac filling pressures (as assessed by echocardiographic E/e') rose slightly, but not significantly postsurgery. Second messenger, hemodynamic, renal, and neurohormonal responses to BNP were not altered between studies. Conclusion: Obesity is associated with increased clearance, but preserved bioactivity, of BNP.